Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1146/annurev.immunol.22.012703.104731
|View full text |Cite
|
Sign up to set email alerts
|

PhysiologicalControl ofImmuneResponse andInflammatoryTissueDamage byHypoxia-InducibleFactors andAdenosineA2AReceptors

Abstract: Immune cell-mediated destruction of pathogens may result in excessive collateral damage to normal tissues, and the failure to control activated immune cells may cause immunopathologies. The search for physiological mechanisms that downregulate activated immune cells has revealed a critical role for extracellular adenosine and for immunosuppressive A2A adenosine receptors in protecting tissue from inflammatory damage. Tissue damage-associated deep hypoxia, hypoxia-inducible factors, and hypoxia-induced accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
463
3
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 642 publications
(485 citation statements)
references
References 110 publications
17
463
3
2
Order By: Relevance
“…It remains to be tested if A 2A R in myeloid cells also play a key role in other brain noxious conditions where the infiltration of these cells into the brain is less well documented. This proposal that the effect of A 2A Rs in myeloid cells is most important for the role of A 2A Rs in the control of brain damage is surprising based on the well established robust role of adenosine in attenuating (rather than exacerbating) inflammation in the periphery ( [294]; reviewed in [295,296]). In fact, adenosine is a potent anti-inflammatory agent with A 2A Rs triggering BOFF^signals in activated immune cells, which constitutes one of the most fundamental and immediate tissue-protecting mechanisms (reviewed in [295,296]).…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionmentioning
confidence: 99%
“…It remains to be tested if A 2A R in myeloid cells also play a key role in other brain noxious conditions where the infiltration of these cells into the brain is less well documented. This proposal that the effect of A 2A Rs in myeloid cells is most important for the role of A 2A Rs in the control of brain damage is surprising based on the well established robust role of adenosine in attenuating (rather than exacerbating) inflammation in the periphery ( [294]; reviewed in [295,296]). In fact, adenosine is a potent anti-inflammatory agent with A 2A Rs triggering BOFF^signals in activated immune cells, which constitutes one of the most fundamental and immediate tissue-protecting mechanisms (reviewed in [295,296]).…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionmentioning
confidence: 99%
“…27 At the height of inflammation, the destruction of host tissue combined with damaged microcirculation and hypoxia leads to elevation of extracellular adenosine. 28 Animal models of asthma, 29 arthritis, 30 sepsis, 31 inflammatory bowel disease 32 and wound healing 33 have helped to elucidate the regulatory roles of adenosine in dictating the development and progression of disease.…”
Section: Pf Inhibits the Functions Of T Cells And Differentiation Of mentioning
confidence: 99%
“…For example, Griffioen et al indicated that tumors downregulate vascular cell adhesion molecule-1 expression on endothelial cells, which modulate immune cells-vessel wall interaction and decrease the effector's cells to enter tumor tissue. 16 Sitkovsky et al 17 showed that hypoxia-induced adenosine and adenosine receptortriggered signaling can block innate and adaptive immune responses to prevent tissues damage from inflammatory damage and also protect cancerous tissues by inhibiting incoming antitumor T lymphocytes, 28 Le et al showed that a novel hypoxia-induced galectin-1 protein modulates tumor immune privilege in vivo. 29 These results suggest that tumor microenvironment may provide a sanctuary for a small number of bacteria that will escape the immune clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Systemically administered bacteria selectively replicated at tumor region may be dependent on various tumor-related factors. For example, tumor may release the regulatory cytokines (IL-10, IL-4, TGFb), 12,13 downregulation of Fas or upregulation of FasL expression to escape immune clearance 14,15 reducing the expression of vascular cell adhesion molecule-1 on endothelial cell to prevent immune effector cells to enter tumor tissue 16 and hypoxia-induced adenosine accumulation suppresses the function of activated immune cells 17 to provide an immunosuppressive or hypoxic environment for bacteria to replicate within tumors. Based on these findings, we wished to test whether bacterial delivery of the prodrug-activating enzyme bG could be achieved to allow selective intratumoral activation of a glucuronide prodrug 9ACG for cancer therapy (Figure 1).…”
Section: Introductionmentioning
confidence: 99%